Exo-nanomaterials in cancer immunotherapy: reprogramming the tumor immune microenvironment - Fang, WeiJian; Qiu, EnDuo; Liu, Rui; Wang, ShanLin; Wang, TianFu; Wang, YuMing (Frontiers in Immunology, 2026)
Immunotherapies such as checkpoint blockade, adoptive cell transfer and vaccines can induce durable responses, yet most solid tumors remain refractory because the tumor immune microenvironment (TIME) is both immunosuppressive and physically difficult to access. In parallel, extracellular vesicles (EVs) and synthetic nanomaterials have emerged as complementary immune messengers and programmable carriers. Exo-nanomaterials, hybrids that fuse EV membranes with synthetic cores, aim to unite EV biocompatibility and trafficking with the loading capacity, modularity and stimulus-responsiveness of engineered nanomaterials. Here, we summarize how exosomes shape the TIME by distributing checkpoint ligands, reprogramming myeloid cells and modulating antigen presentation, and how nanomaterials are engineered to improve tumor-localized delivery of innate agonists and vaccine cargos. We then outline major construction routes (coating, loading and mimetic fabrication) and design modules that enable cold-to-hot conversion, sensitization to checkpoint blockade, and delivery of neoantigen and nucleic-acid vaccines. Finally, we discuss key translational challenges, including standardization, mechanism deconvolution, scalable manufacturing and safety, and propose immune-by-design principles to guide reproducible, mechanism-grounded development toward durable immunotherapy in solid tumors.